Blended Learning for ELT - Pardede, Parlindungan (JET (Journal of English Teaching), 2012)
Information and communication technology (ICT) has grown exponentially during the past three decades considerably changed many aspects in industrial and trading sectors. Currently, it is revolutionizing education. One of the most important results of the revolution is the emergent of blended learning, which combines the best of face-to-face and ICT application. This article reviews current ideas, practices, and empirical information concerning the nature of blended learning in general and Computer Assisted Language Learning (CALL), a version of blended learning particularly used in English Language Teaching (ELT), in particular. All of these will hopefully enrich creative ideas for implementing blended learning in ELT to enhance our student’s achievement.